2016
DOI: 10.1002/clen.201300454
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Mobilization and Distribution of Selenium in a Soil/Water/Air System: A Global Perspective With Special Reference to the Indian Scenario

Abstract: Narrow tolerance limit of selenium (Se) brings serious concerns through deficiency as well as toxicity in the biological and environmental systems. Both geogenic and anthropogenic activities govern Se origin in nature, while its bioavailability is controlled by biogeochemical conditions and nature of Se species. Selenium hazards have drawn a special research interest globally, especially in USA, Canada and China, where large populations of aquatic life and human beings are being severely affected. Both Se defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 102 publications
(258 reference statements)
0
11
0
4
Order By: Relevance
“…Also, Figures 2 and 3 show that these elements exhibited increased levels either in coal or ash material. Similarly, Paikaray (2016) reported that many areas in India show Se toxicity having resulted from coal mining and coal-fired power plants. The author emphasised that the problem can be regarded as being even more serious when taking into account that India is the third largest global coal producer.…”
Section: Aquatic and Herbal Geochemistrymentioning
confidence: 99%
“…Also, Figures 2 and 3 show that these elements exhibited increased levels either in coal or ash material. Similarly, Paikaray (2016) reported that many areas in India show Se toxicity having resulted from coal mining and coal-fired power plants. The author emphasised that the problem can be regarded as being even more serious when taking into account that India is the third largest global coal producer.…”
Section: Aquatic and Herbal Geochemistrymentioning
confidence: 99%
“…In water, selenium is present in trace quantities, and mainly in the form of selenates and selenites [16]. The amount of selenium in groundwater is much higher than that in seawater [13] because of selenium elution from the parent rocks and excessive fertilization of soils with mixtures rich in selenium compounds [17]. The selenium content determined in groundwater in Poznań (Poland) is 0.17–0.44 µg/L [18].…”
Section: Occurrence Of Selenium In the Environmentmentioning
confidence: 99%
“…It penetrates the soil as a result of anthropogenic activity through the combustion of coal and lignite, crude oil, and the use of agrotechnical processes—fertilization or liming [14]. These treatments are being done for example in Hubei Province, an area of Enshi in China, where the selenium content in coal oscillates at the level of 6–8.4 g/kg [17]. However, the greater part of China surface exhibits a very low content of this element in the soil (<0.1 mg/kg).…”
Section: Occurrence Of Selenium In the Environmentmentioning
confidence: 99%
“…So, the amount in similar food item varies in different geographical locations. However, the primary sources for this element are meat, bread, mushrooms, dairy products, fish, seafood, and nuts [ 49 , 50 , 51 ]. It acts as an enzyme cofactor that takes part in mammalian redox reactions [ 52 ].…”
Section: Minerals and Immune Systemmentioning
confidence: 99%